IMPLEMENTATION OF REST API ARCHITECTURE FOR FEELSQUEST ONLINE COURSE FEATURE IN FEELSBOX APPLICATION USING LARAVEL FRAMEWORK - Riawan, Faza Alexander; Kusumo, Dana Sulistyo; Selviandro, Nungki (Jurnal Teknik Informatika (Jutif), 2024)
Feelsbox is a digital-based startup that focuses on the importance of mental health issues and offers innovative solutions to help people maintain their mental health. FeelsBox took the initiative to develop an online course feature "FeelsQuest" with the aim of providing education and helping prevent and overcome mental health problems to the wider community, especially teenagers. The development of this feature uses the PHP programming language with the Laravel framework and implements the REST API architecture. The choice of REST API architecture is based on the concept of separation of responsibilities so that the API can be reused on different platforms. In addition, a suitable test is needed to test the REST API that has been built. Testing of the REST API that has been built is done with the API testing method which is focused on aspects of functionality and performance using Postman to ensure that the API built produces responses and behaves according to the needs of the FeelsQuest feature of the FeelsBox application. The test results show that the implementation of the REST API on the FeelsQuest feature is in accordance with the functional requirements and successfully applies the concept of separation of concerns and meets the non-functional needs of the FeelsQuest feature related to the response time of each API, which is under 3 seconds.